EMOCIONAL KONCEPTLERDI SALÍSTÍRMALÍ IZERTLEWDIŃ TEORIYALÍQ TIYKARLARÍ (INGLIS HÁM QARAQALPAQ TILLERI MATERIALÍNDA) - Xalmuratov, Ikram Dawletbaevich (SCIENCE and SOCIETY, 2026)
This article is dedicated to the theoretical analysis of emotional concepts and the mechanisms of their verbalization within English and Karakalpak linguocultures. The work is grounded in the fundamental principles of linguopragmatics and cognitive linguistics. The research emphasizes that emotional units in literary texts are not static markers; rather, they perform vital pragmatic functions, such as orienting the reader and conveying the author’s stance. The work contributes to the development of comparative language typology and linguoculturology.